2020
DOI: 10.3390/ijms21165881
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Poly(ethylene-co-vinyl alcohol)/poly(ε-caprolactone) Blend for Bioscaffolding Applications

Abstract: In order to improve the cell adhesion on poly(ε-caprolactone) (PCL) scaffolds, poly(ethylene-co-vinyl alcohol) (E-VAL) which has hydroxyl groups capable of developing hydrogen bonds with celling was blended with this polymer. To reach this goal, a series of E-VAL/PCL blends with different compositions were prepared by the solvent casting method. The miscibility of the polymer blend was proved by differential scanning calorimetry and Fourier-transform infrared spectroscopy spectrometry. Furthermore, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…When the content of PEVAL in the blend was more than 50% by weight, the decrease in the adhesion performance was due to the reduction in the size of the pores on the surface of the resulting material caused by the excessive attraction forces created by increasing the density of the hydroxyls of the polymeric blend. Similar results were also obtained by Alghamdi et al [ 70 ] in an investigation that involved PEVAL and PCL.…”
Section: Resultssupporting
confidence: 89%
“…When the content of PEVAL in the blend was more than 50% by weight, the decrease in the adhesion performance was due to the reduction in the size of the pores on the surface of the resulting material caused by the excessive attraction forces created by increasing the density of the hydroxyls of the polymeric blend. Similar results were also obtained by Alghamdi et al [ 70 ] in an investigation that involved PEVAL and PCL.…”
Section: Resultssupporting
confidence: 89%
“…The miscibility of the E-VAL/PCL mixture with different compositions was recently proven by DSC and confirmed by Fourier-transform infrared (FTIR) analysis in our previous study [33]. The DSC analysis revealed the presence of a single T g in the thermograms of the blends and its negative deviation from that of the ideal, and these indicated the interaction between the chains of different natures.…”
Section: Miscibilitysupporting
confidence: 64%
“…47 EVAL is a copolymer in which the presence of hydroxyl groups promotes cell adhesion due to the hydrophilic character of the cells. 48 Alghamdi et al found that the poly(ε-caprolactone) matrix incorporated with EVAL presents a typical stress−strain pattern that is specific to a highly porous scaffold. 48 In available tests, the PEGDA hydrogels are generally non-toxic to DP aggregates, and increasing the stiffness of the gel has no significant effect on their cell viability.…”
Section: Mechanical Properties Of the Substratementioning
confidence: 99%
“…48 Alghamdi et al found that the poly(ε-caprolactone) matrix incorporated with EVAL presents a typical stress−strain pattern that is specific to a highly porous scaffold. 48 In available tests, the PEGDA hydrogels are generally non-toxic to DP aggregates, and increasing the stiffness of the gel has no significant effect on their cell viability. It can be modified that changing the concentration of PEGDA can alter the mechanical stiffness of the microgel.…”
Section: Mechanical Properties Of the Substratementioning
confidence: 99%